Study of Physicochemical Properties of Polystyrene Concrete Based on Fly Ash and Water from Hydro-Ash Removal Facilities - Aslan Maikonov; Rimma Niyazbekova; Lazzat Shansharova; Bakytzhan Salimov; Vasiliy Mikhalchenko; Valeriy Khan (Chemical Engineering Transactions, 2024)
The article is devoted to improving the physical and chemical characteristics of polystyrene concrete by the means of adding industrial waste, thereby reducing the negative impact of ash and slag waste from thermal power plants (TPPs) of Kazakhstan on the environment. Fly ash, generated in large quantities as a result of fuel combustion at power plants, negatively affects the environment, polluting the air, soil, sewage, etc. The article presents the results of the study of the chemical composition of ash and slag waste. Possible ways of ash utilization are considered. Also, the effects of adding the fly ash and water from hydro-ash removal facilities on the physical and mechanical characteristics of cement was investigated. For this purpose, samples with the addition of 5-10-15 % of fly ash by a weight of the prepared cement mixture. All samples of 3-7-28 curing days were tested. In the article standardized methods of cement dough testing were implemented: determination of standard consistency, setting time of cement dough, and determination of physical and mechanical parameters of concrete specimens in accordance with normative documents. The results of studies of the physical and mechanical properties of cement dough with the addition of fly ash from the ash dump and water from the hydro-ash removal facilities of TPP (thermal power plant) are given. The results of studies of standard consistency, setting time of cement dough, as well as tests of concrete compressive strength are given.